Relationship Marketing:Pengaruhnya terhadap Retensi Pelanggan (Studi pada Restoran di Surabaya) - Prasetyo Hadi; Djumilah Zain; Mintarti Rahayu; Munawar Ismail (Jurnal Aplikasi Manajemen, 2012)
The research aims at knowing (1) Customer Relationship Marketing in maintaining customer retention, (2) The influence of service quality, customer value and satisfaction as a mediation of Customer Relationship Marketing on customer retention. The data are analyzed by using Structural Equation Modeling (SEM). The research findings show that (1) stimulating Relationship Marketing which cannot cater for customer expectation in all aspects will not increase customer retention; (2) Relationship Marketing (RM) is able to contribute to the enterprise success in maintaining the customers through an excellent service quality; (3) the implementation of Relationship Marketing through the activity of excellent customer value will contribute to the implementation of Relationship Marketing towards customer retention, (4) the ability of entrepreneurs to exclusively give satisfaction in the activity of Relationship Marketing is a crucial aspect to maintain customer retention.Keywords: Relationship Marketing, Service Quality, Customer Value, Customer Satisfaction and Customer Retention